MOTIVATIONAL FACTORS OF NATIONAL IDENTITY IN PROFESSIONAL ACTIVITY - Kobilov , Uchkun (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
National identity plays a significant role in shaping individual motivation and professional activity in today’s globalized environment. While globalization encourages cultural integration, it also highlights the importance of national identity as a source of pride, belonging, and inspiration. Professionals often draw upon their cultural roots, traditions, and national values to strengthen their commitment to their work and contribute meaningfully to society. This paper examines the motivational factors of national identity within professional activity, exploring dimensions such as cultural pride, collective responsibility, language, and values. It argues that national identity does not hinder professional growth but serves as a catalyst for resilience, innovation, and dedication. Understanding these motivational factors is essential for policymakers, educational institutions, and organizations seeking to enhance professional productivity while preserving cultural uniqueness.